Determinants of Local Original Income in Sulawesi with Investment as an Intervening Variable - Rauf, Rahma; Retno Dwi Hastuti, Diah; Syafri, Muhammad (Jurnal Ilmu Ekonomi JIE, 2025)
The purpose of this study is to analyse the factors that influence Regional Original Revenue in six provinces on the island of Sulawesi, with investment as an intervening variable. This study uses a quantitative approach, including panel-data regression analysis and the Sobel test, for the period from 2015 to 2024. The results of this study indicate that population size, gross regional domestic product, and investment have a significant direct effect on local revenue. Gross Regional Domestic Product, in addition to having a direct impact, also has an important indirect effect on Local Own-Source Revenue. In contrast, inflation has no considerable impact either directly or indirectly. This study emphasises the importance of increasing Investment, developing strategic sectors, and improving the quality of human resources to optimise Local Own-Source Revenue. This study offers a new perspective on the role of investment as an intervening variable in the relationship between local revenue factors on the island of Sulawesi.